Sociopreneurship Berbasis Inovasi Sosial: Strategi Pemberdayaan Ekonomi Pondok Pesantren Melalui Peran Perempuan Dalam Pengembangan Produk Berbahan Dasar Ikan - Fitriyah Noor, Huriyatul; Hudaidah, Siti; Caesario, Rachmad; Yulianto, Herman; Camelia, Nita (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Along with the rapid advancement of digital information technology, various sectors are driven to adapt through innovation, including efforts to strengthen economic empowerment. Social-innovation-based sociopreneurship serves as an appropriate approach to addressing economic challenges while also generating positive social impact. This study focuses on applying social-innovation-based sociopreneurship strategies to enhance economic empowerment at Pondok Pesantren Al Hikmah Bandar Lampung, by involving women in product development activities. The research aims to introduce, reinforce, and implement economic empowerment strategies rooted in social innovation by utilizing the potential of women. The activities were carried out through six stages: (1) delivery of educational materials, (2) design of social-innovation-based marketing strategies, (3) introduction to information-technology-based marketing, (4) understanding women’s potential in marketing, (5) creation of digital marketing media, and (6) development of innovative marketing content. It is expected that this program will increase the knowledge and practical skills of women at Pondok Pesantren Al Hikmah Bandar Lampung, enabling them to optimize their roles in product development and marketing. Ultimately, this initiative is expected to foster economic independence based on sociopreneurship within the pesantren.